Wokół kategorii „uczestnictwa” – rozważania w perspektywie myśli społecznej Karola Wojtyły - Ecler-Nocoń, Beata (Studia Edukacyjne, 2020)
This study analyzes the usefulness of the theory of participation as put forth by Karol Wojtyła. The author describes two dimensions of participation in the community: the first“me” “others” and the second: “us”. The article shows the constructive mechanisms of community development such as dialogue, solidarity and opposition and the patterns which impede development of communities and men, such as conformism and alienation. In the conclusions, the author postulates implementing Karol Wojtyła’s theory of participation in education.